Impact of blood pressure changes and course on hematoma growth in acute intracerebral hemorrhage. Issue 9 (5th May 2013) - Rodriguez‐Luna, D.; Piñeiro, S.; Rubiera, M.; Ribo, M.; Coscojuela, P.; Pagola, J.; Flores, A.; Muchada, M.; Ibarra, B.; Meler, P.; Sanjuan, E.; Hernandez‐Guillamon, M.; et al.
Abstract : Background and purpose: An association between high blood pressure (BP) in acute intracerebral hemorrhage (ICH) and hematoma growth (HG) has not been clearly demonstrated. Therefore, the impact of BP changes and course on HG and clinical outcome in patients with acute ICH was determined. Methods: In total, 117 consecutive patients with acute (<6 h) supratentorial ICH underwent baseline and 24‐h CT scans, CT angiography for the detection of the spot sign and non‐invasive BP monitoring at 15‐min intervals over the first 24 h. Maximum and minimum BP, maximum BP increase and drop from baseline, and BP variability values from systolic BP (SBP), diastolic BP and mean arterial pressure (MAP) were calculated. SBP and MAP loads were defined as the proportion of readings >180 and >130 mmHg, respectively. HG (>33% or >6 ml), early neurological deterioration (END) and 3‐month mortality were recorded. Results: Baseline BP variables were unrelated to either HG or clinical outcome. Conversely, SBP 180‐load independently predicted HG (odds ratio 1.05, 95% CI 1.010–1.097, P  =   0.016), whilst both SBP 180‐load (odds ratio 1.04, 95% CI 1.001–1.076, P  =   0.042) and SBP variability (odds ratio 1.2, 95% CI 1.047–1.380, P  =   0.009) independently predicted END. Although none of the BP monitoring variables was associated with HG in the spot‐sign‐positive group, higher maximum BP increases from baseline and higher SBP and MAP loads were significantly related to HG in the spot‐sign‐negative group. Conclusions: In patients with acute supratentorial ICH, SBP 180‐load independently predicts HG, whilst both SBP 180‐load and SBP variability predict END.